Meningkatkan Kemampuan Membaca Pemahaman Dengan Menggunakan Metode Speed Reading Pada Siswa Kelas V SD Negeri 1 Poka: Indonesia - Ningsih; Ririhena, Ribka L; Sahetapy, Sarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine how to improve reading comprehension skills using the Speed Reading method in grade V students of SD Negeri 1 Poka in the 2024/2025 academic year. This study was a Classroom Action Research (CAR). The subjects were 19 grade V students. The results showed that using the Speed Reading learning method can improve students' reading comprehension skills. The study revealed that the average student learning outcome score in the pre-action phase increased from 53.05% to 63.68% in Cycle I, and in Cycle II, increased to 83.50%. Based on the research results, it can be concluded that in cycle II, students have classically completed their learning, as 83.50% of students obtained a score of 70 or higher, exceeding the desired completion percentage of 70%. This proves that the use of the Speed Reading method can improve the reading comprehension skills of fifth-grade students at SD Negeri 1 Poka in the 2024/2025 academic year.